Review Essay: The Films of Simone Rapisarda Casanova - Dickinson, Peter (Anthropologica, 2020)
This essay examines three feature-length works by Italian-Canadian experimental film maker Simone Rapisarda Casanova. I discuss how Rapisarda’s collaborative and process-driven methods draw from a tradition of “shared ethnographic” filmmaking advanced by Jean Rouch, but also how Rapisarda innovates this tradition through his aesthetic and technical choices.